Preferensi Pembelian Green Product: Eksplorasi Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Produk Tisu Tessa - Lestari, Dita Sri; Setiyaningrum, Ika Feni (Journal of Economics and Business Research (JUEBIR), 2023)
The purpose of this study was to determine the effect of: (1) environmental awareness on green product purchasing decisions, (2) eco-labelling on green product purchasing decisions, (3) green brand image on green product purchasing decisions. This study uses quantitative research methods. The population in this study were consumers of Tessa Wipes in Karanganyar Regency. The sampling technique in this study used a non-probability sampling method. The samples taken in this study were 100 respondents. Data analysis techniques used instrument testing, classical assumption testing, model accuracy testing, multiple linear regression testing and hypothesis testing with the help of the SPSS version 23 application. The results of this study indicate that: (1) environmental awareness has a positive and significant effect on green product purchasing decisions. This is evidenced by the results of multiple linear regression with a value of 0.31, a calculated t value of 2.244 > t table of 1.660 and a significance value of 0.027 <0.05, (2) eco-labelling has a positive and significant effect on green product purchasing decisions. This is evidenced by the results of multiple linear regression with a value of 0.277, a calculated t value of 2.145 > t table of 1.660 and a significance of 0.034 <0.05, (3) green brand image has a positive and significant effect on purchasing decisions for green products. This is evidenced by the results of multiple linear regression that green brand image has a value of 0.511, a t-value of 4.590 > t-table of 1.984 and a significance of 0.000 <0.05